Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae) - Qin, Yanyan; Liu, Xianwei; Li, Kai (Zootaxa, 2016)
A review of the rhaphidophorid genus Tamdaotettix Gorochov, 1998 is presented. One new species, one newly-recorded species from China and one species from Vietnam are identified and described. These are namely Tamdaotettix (Tamdaotettix) tridenticulatus sp. nov., Tamdaotettix (Laotettix) curvatus Gorochov, 2015 and Tamdaotettix (Tamdaotettix) semipullus Gorochov, 1998. At the same time, Megadiestramima extensa Gorochov, 1998 is redescribed. A key to the species of Tamdaotettix is provided.